Glacial fluctuations in tropical Africa during the last glacial termination and implications for tropical climate following the Last Glacial Maximum. (1st September 2020) - Jackson, M.S.; Kelly, M.A.; Russell, J.M.; Doughty, A.M.; Howley, J.A.; Chipman, J.W.; Cavagnaro, D.A.; Baber, M.B.; Zimmerman, S.R.H.; Nakileza, B.
Abstract: The tropics are a dynamic component of the global climate system and exert a profound influence on modern climate variability. Yet the role of the tropics in past climate changes, for example during the last glacial termination, is uncertain. This uncertainty is due in part to the relative paucity of terrestrial temperature records from the tropics, which hinders efforts to understand the mechanisms that influenced deglacial warming and abrupt climate events. Tropical glaciers are sensitive to changes in climate, and mapping and dating past tropical glacial fluctuations provides a valuable record of terrestrial climate changes in the low latitudes. We report a chronology of past glacial extents in the Rwenzori Mountains of Uganda (0.3°N, 29.9°E) based on 51 beryllium-10 ( 10 Be) surface-exposure ages from three separate glacial catchments. Results indicate that Rwenzori glaciers retreated considerably during Heinrich Stadial 1. The rate of net glacial recession slowed between ∼15 and 11 ka, although glaciers continued to retreat during this period. Rwenzori glaciers then retreated more rapidly during the early Holocene. The Rwenzori glacial chronology is broadly similar to glacial chronologies reconstructed elsewhere in East Africa and in tropical South America. We suggest that this similarity may reflect coherent, tropics-wide temperature fluctuations during the last deglaciation. The Rwenzori glacial chronology provides crucial information on the global footprint of deglacial warming and abrupt climate events and, thus, the potential mechanisms that influenced tropical climate during the last glacial termination. Highlights: Chronology of past glacial extents in the Rwenzori Mountains of Uganda (0.3°N, 30°E). Based on 51 10Be surface-exposure ages from three separate glacial catchments. Glaciers in the Rwenzori Mountains retreated during Heinrich Stadial 1. Rwenzori chronology provides crucial information on deglacial warming in the tropics.